2018
DOI: 10.2147/copd.s176122
|View full text |Cite
|
Sign up to set email alerts
|

Role of inflammatory cells in airway remodeling in COPD

Abstract: COPD is characterized by chronic bronchitis, chronic airway obstruction, and emphysema, leading to a progressive and irreversible decline in lung function. Inflammation is central for the development of COPD. Chronic inflammation in COPD mainly involves the infiltration of neutrophils, macrophages, lymphocytes, and other inflammatory cells into the small airways. The contribution of resident airway structural cells to the inflammatory process is also important in COPD. Airway remodeling consists of detrimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
184
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 254 publications
(210 citation statements)
references
References 89 publications
2
184
0
5
Order By: Relevance
“…He also reported that immune cells can control the stages of cancer development at all stages [22]. COPD including emphysema is a chronic inflammatory disease, in which neutrophils, monocytes, macrophages, and lymphocytes are infiltration in airway and lung tissue [23]. In addition, COPD and lung cancer are progressive diseases caused by substances that mediate this inflammatory response, which is supported by the high incidence of lung cancer in patients with severe impaired lung function and frequent exacerbations with inflammatory reactions [14].…”
Section: Discussionmentioning
confidence: 99%
“…He also reported that immune cells can control the stages of cancer development at all stages [22]. COPD including emphysema is a chronic inflammatory disease, in which neutrophils, monocytes, macrophages, and lymphocytes are infiltration in airway and lung tissue [23]. In addition, COPD and lung cancer are progressive diseases caused by substances that mediate this inflammatory response, which is supported by the high incidence of lung cancer in patients with severe impaired lung function and frequent exacerbations with inflammatory reactions [14].…”
Section: Discussionmentioning
confidence: 99%
“…The umbrella term Chronic Obstructive Pulmonary Disease (COPD) is used to describe a set of symptoms mainly chronic bronchitis and airway obstruction, remodeling of the small airways, and emphysema, which results in an irreversible decline in the function of the pulmonary system [36]. Infiltration of a variety of inflammatory cell types including neutrophils and macrophages into the small airways is a common finding in COPD [36]. Ekberg-Jansson et al investigated the distribution of MCs in different bronchial compartments of 29 asymptomatic smokers and 16 healthy non-smokers.…”
Section: Role Of Mcs In the Pathology Of Copdmentioning
confidence: 99%
“…Cathepsin G, NE and PR3 have also been reported to contribute towards mucus hypersecretion [128,129]. NETs secreted by activated neutrophils, contain histones, NE and MPO, and are found to be excessive in COPD patients, contributing to disease progression [130].…”
Section: Granulocyte-targeted Therapies For Asthmamentioning
confidence: 99%